Anxiety among adolescent survivors of pediatric cancer: A missing link in the survivorship literature. Issue 2 (28th April 2014) - McDonnell, Glynnis; Baily, Charles; Schuler, Tammy; Verdeli, Helen
Abstract: Objective: With growing numbers of pediatric cancer survivors, it is becoming increasingly important to investigate the psychosocial sequelae of surviving cancer diagnosed during childhood or adolescence. It is particularly important to study the psychosocial needs of adolescent survivors of pediatric cancer because adolescence is a critical time during psychosocial development. Although there is existent literature about the general psychosocial adjustment of this population, the literature regarding anxiety is scant. This brief review aimed to assesses currently available literature that addresses anxiety in adolescent cancer survivors. Method: Articles assessing psychosocial adjustment in adolescent survivors of pediatric cancer were reviewed for information regarding anxiety symptoms. Results: To the authors' knowledge, there is no literature that focuses specifically on anxiety in this population. However, many articles reported results that indicated the possibility of increased anxiety in this group. Significance of results: It is critical to further investigate anxiety in this group and develop appropriate interventions if necessary. Doing so will aid the process of enhancing psychosocial care for adolescent cancer survivors.